Analisis Kemampuan Awal Matematis dan Kesalahan Mahasiswa Berdasarkan Newman’s Error Analysis pada Materi Luas Bangun Datar - Aida Sari, Fitri (Program Studi Pendidikan Guru Sekolah Dasar, FKIP, Universitas Mulawarman, 2025)
Understanding fundamental mathematical concepts, particularly the area of plane figures, is crucial for students of the elementary school teacher education study program. Despite learning these concepts since elementary school, many of them still struggle to fully understand it. This study aims to identify the mathematical prior knowledge students in the area of plane figures and the types of errors they make using the Newman Error Analysis (NEA) approach. The research employs a descriptive quantitative method with instruments comprising essay tests and interviews. The study subjects consisted of 35 students from an elementary school teacher education study program in East Kalimantan. Results reveal that 67.7% of the students possess moderate mathematical prior knowledge, while the rest fall into the low and high categories. The most common errors occur in the comprehension and transformation stages, indicating difficulties in understanding problems and converting information into mathematical forms. The implications of this research emphasize the importance of appropriate learning strategies or models to strengthen students' understanding of basic mathematical concepts.